2018
DOI: 10.1021/acsomega.8b03132
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of the OPLSAA Force-Field for Liquid Alcohols

Abstract: We employ the popular all-atom optimized potential for liquid simulations, OPLSAA, force-field to model 17 different alcohols in the liquid state. Using the standard simulation protocol for few hundred nanosecond time periods, we find that 1-octanol, 1-nonanol, and 1-decanol undergo spontaneous transition to a crystalline state at temperatures which are 35–55 K higher than the experimental melting temperatures. Nevertheless, the crystal structures obtained from the simulations are very similar to those determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 50 publications
2
40
0
Order By: Relevance
“…The OPLS-AA wet octanol system underwent a phase transition to a dense solid phase during the simulation at 273 K (Figure 2a). The experimental melting temperature of pure octanol is 258.5 K and although water-octanol mixtures will have a different melting temperature, the behavior that we observed here is likely unphysical because similar behavior was recently reported and considered a consequence of exaggerated attractive interactions between the alkane chains of the alcohols in standard OPLS-AA [48]. Because we observed no phase transition in simulations at temperatures around our simulation temperature (300 K) we used the standard OPLS-AA parameters of octanol for the OPLS-AA calculations in this work.…”
Section: Validation Of Octanol Parameterssupporting
confidence: 75%
“…The OPLS-AA wet octanol system underwent a phase transition to a dense solid phase during the simulation at 273 K (Figure 2a). The experimental melting temperature of pure octanol is 258.5 K and although water-octanol mixtures will have a different melting temperature, the behavior that we observed here is likely unphysical because similar behavior was recently reported and considered a consequence of exaggerated attractive interactions between the alkane chains of the alcohols in standard OPLS-AA [48]. Because we observed no phase transition in simulations at temperatures around our simulation temperature (300 K) we used the standard OPLS-AA parameters of octanol for the OPLS-AA calculations in this work.…”
Section: Validation Of Octanol Parameterssupporting
confidence: 75%
“…Intra-molecular interactions within graphene flakes were described by the AIREBO potential 65 . For 1-octanol and cyclohexane two recently developed models were used that are based on the Opls forcefield [66][67][68] . These two models were specifically refined on reproducing thermodynamic properties such as the bulk density.…”
Section: Methodsmentioning
confidence: 99%
“…Another likely reason for the underestimation of the dielectric constant is the neglect of polarizability, which is common to most molecular models available to date. This hypothesis is supported by the fact that several transferable force fields also underestimate the dielectric constant [21][22][23].…”
Section: Pure Fluidsmentioning
confidence: 89%
“…Núñez-Rojas et al [22] carried out a similar study on the TraPPE/UA force field and also found that the dielectric constant is typically underestimated, with an average deviation of about 37%. Zangi [23] investigated the OPLS/AA force field for alcohols, and found an average underestimation of the dielectric constant of about 33%. Including experimental data on the dielectric constant in the model parametrization has been suggested only recently [24,25].…”
Section: Introductionmentioning
confidence: 99%